Modulation of Cystatin C in Human Macrophages Improves Anti-Mycobacterial Immune Responses to Mycobacterium tuberculosis Infection and Coinfection With HIV - Pires, David; Calado, Marta; Velez, Tomás; Mandal, Manoj; Catalão, Maria João; Neyrolles, Olivier; Lugo-Villarino, Geanncarlo; Vérollet, Christel; Azevedo-Pereira, José Miguel; Anes, Elsa (Frontiers in Immunology, 2021)
Tuberculosis owes its resurgence as a major global health threat mostly to the emergence of drug resistance and co-infection with human immunodeficiency virus (HIV). The synergy between HIV and Mycobacterium tuberculosis (Mtb) modifies the host immune environment to enhance both viral and bacterial replication and spread. In the lung immune context, both pathogens infect macrophages establishing favourable intracellular niches. Both manipulate the endocytic pathway in order to avoid destruction. Relevant players of the endocytic pathway to control pathogens include endolysosomal proteases, cathepsins, and their natural inhibitors, cystatins. Here, a mapping of the human macrophage transcriptome for type I and II cystatins during Mtb, HIV or Mtb-HIV infection displayed different profiles of gene expression revealing cystatin C as a potential target to control mycobacterial infection as well as HIV co-infection. We found that cystatin C silencing in macrophages significantly improves the intracellular killing of Mtb, which was concomitant with an increased general proteolytic activity of cathepsins. In addition, downmodulation of cystatin C led to an improved expression of the HLA class II in macrophages and an increased CD4+ T-lymphocyte proliferation along with enhanced IFN-γ secretion. Overall, our results suggest that the targeting of cystatin C in human macrophages represents a promising approach to improve the control of mycobacterial infections including MDR-TB.